Study of gall s tone composition in North Karnataka - S, Kalghatgi; Aravind, K; Kulkarni, Mukund; T, Vipin; B, Sanganal (Surgical Review: International Journal of Surgery, Trauma and Orthopedics, 2017)
Introduction: Gall stone disease is common problem in Indian subcontinent. While majority of gallstone disease are cholesterol in north India (similar to western world) they are predominantly pigment or mixed type in south India. There are recent reports of changing trends in composition of gallstones with a shift towards cholesterol gall stones especially in south Asian countries, and this has been attributed to changes in life style and dietary factors. Material and Methods: Descriptive analytic study were conducted on39 gallstones from KIMS, HUBLI hospital were analysed by semiquantitative titrimetric and colourimetric methods over a period of 18 months from dec 2014 to 2016.The proportion of different types of gallstones was described using 95% confidence interval based on exact method. Results: The biliary calculi collected from 39 gallstone patients were divided into 3 groups based on their colour: cholesterol calculi, mixed calculi and pigment calculi. Out of the 39 stones collected , 15 were mixed calculi, 14 were pigment calculi and 10 were cholesterol calculi indicating the incidence of gallstones in the studied population from KIMS, Hubli as follows : Mixed calculi (38%) > pigment calculi ( 36%)> cholesterol calculi (26%). The incidence of gallstone was higher in age group 41-50 yrs followed by 51- 60 yrs and 31-40 yrs in which females were higher than males. Conclusion: A quantitative chemical analysis of total cholesterol, total bilirubin, fatty acids, triglycerides, phospholipids, bile acids, soluble proteins, sodium potassium, magnesium, copper, oxalate and chlorides of biliary calculi (10 cholesterol, 15 mixed and 14 pigment) retrieved from surgical operation of 39 patients from KIMS, Hubli hospital was carried out. Although total cholesterol was a major component of cholesterol, mixed and pigment gall stone in KIMS, Hubli, the content of most of the other lipids, cations and anions was different in different gall stones indicating their different mechanism of formation.